Performance analysis of NSA control plane and user plane delay in 5G network - Dan ZHANG; Lei WANG; Xiaoqi WANG; Siyu XI (Dianxin kexue)
Different from 2G/3G/4G,the 5G network architecture contains two parts:NSA (non-standalone) and SA (standalone) networking.NSA can help network deploys faster.Low latency is a very important feature of 5G,and its implementation requires a combination of technologies.Based on the 2.6 GHz NR frame structure,combined with theoretical analysis and real case,the current situation and problems of control plane delay and user plane delay were discussed,and the delay optimization method was provided,which provided the corresponding ideas and suggestions for NSA network deployment.